Micronutrients and Anaemia (Journal of Health, Population and Nutrition, 2009)
Micronutrient deficiencies and anaemia remain as major health concerns for children in Bangladesh. Among the micronutrient interventions, supplementation with vitamin A to children aged less than five years has been the most successful, especially after distribution of vitamin A was combined with National Immunization Days. Although salt sold in Bangladesh is intended to contain iodine, much of the salt does not contain iodine, and iodine deficiency continues to be common. Anaemia similarly is common among all population groups and has shown no sign of improvement even when iron-supplementation programmes have been attempted. It appears that many other causes contribute to anaemia in addition to iron deficiency. Zinc deficiency is a key micronutrient deficiency and is covered in a separate paper because of its importance among new child-health interventions. Key words: Anaemia; Anaemia, Iron-deficiency; Iodine deficiency; Iron deficiency; Interventions; Micronutrients; Vitamin A deficiency; Bangladesh doi:10.3329/jhpn.v26i3.1900 J Health Popul Nutr 2008 Sept:26(3): 340-355